Pendidikan Kesehatan Menggunakan Media Booklet + Aplikasi SDIDTK Efektif Meningkatkan Kemandirian Keluarga dalam Pemantauan Tumbuh Kembang Balita - Marwasariaty Marwasariaty; Titin Sutini; Suhendar Sulaeman (Journal of Telenursing (JOTING), 2019)
This study aims to identify the effect of health education using booklet media and SDIDTK application media on family independence in monitoring the growth and development of children under five in the work area of ​​West Bajo Health Center. This study uses Quasi Experimental with a pre and post-test approach without control. The results showed that there was an effect of health education using Booklet media (Δ = 6.80, p value = 0.012), SDIDTK application media (Δ = 7.90, p value = 0.007) Booklet media + SDIDTK Application (Δ = 10.80, p value = 0.005) of family independence in monitoring growth and development. Conclusion, the average score of family independence is very good in the health education intervention group by using the booklet + SDIDTK application because it shows the highest increase so it is recommended to use the media booklet + SDIDTK application for health education related to stimulation, detection and growth and intervention in infants. . Keywords: SDIDTK Application, Booklet, Family Independence, Growth and Development